Affordances theory in multilingualism studies - Aronin, Larissa; Singleton, David (Studies in Second Language Learning and Teaching, 2012)
The concept of affordances originating in Gibson’s work (Gibson, 1977) is gaining ground in multilingualism studies (cf. Aronin and Singleton, 2010; Singleton and Aronin, 2007; Dewaele, 2010). Nevertheless, studies investigating affordances in respect of teaching, learning or using languages are still somewhat rare and tend to treat isolated aspects of multilingualism. This is despite the fact that the theory of affordances can actually provide a valuable, supplementary, up-to-date framework within which a clearer, sharper description and explication of the intriguing range of attributes of multilingual communities, educational institutions and individuals, as well as teaching practices, become feasible. It is important that not only researchers and practitioners (teachers, educators, parents, community and political actors) but also language users and learners themselves should be aware of how to identify or, if necessary, design new affordances for language acquisition and learning. The aim of this article is to adapt the concept of affordances to multilingualism studies and additional language teaching, and in so doing advance theoretical understanding in this context. To this end the article contains a brief summary of the findings so far available. The article also goes further into defining the ways of how affordances work in relation to multilingualism and second language teaching and puts forward an integrated model of affordances.